Is reflux hypersensitivity truly a functional gastrointestinal disorder? A retrospective cross-sectional study. - Yanping Wu; Siyu Liao; Tianyao Qu; Jiaxuan Zhou; Fei Dai; Bin Qin; Xiaoyu Xu; Jun Zhang; Yan Cheng (PLoS ONE)
Background According to Rome IV, reflux hypersensitivity (RH) represents a novel form of functional esophageal disorder. This study was designed to compare the clinical features of three types of endoscopic-negative heartburn: RH, nonerosive reflux disease (NERD), and functional heartburn (FH). Methods Patients with heartburn in a medical center from 01/01/2017 to 10/31/2021 were included. This article presented a blinded retrospective analysis of 24 h MII-pH and HRM tracings from patients with NERD, RH, and FH to compare their clinical characteristics. Results A total of 118 patients were included in the study. There were no significant differences in age, sex, BMI, smoking status, or drinking history among RH, NERD and FH. Functional dyspepsia (FD) symptoms were more prone to exist in FH than in NERD (P < 0.05), whereas hiatal hernia was more prevalent in NERD and RH than in FH (P < 0.05). The incidence of anxiety and depression gradually increased in the NERD, RH, and FH groups (P >  0.05). The distal MNBI and PSPW index of the NERD and RH groups were lower than those of the FH group (P < 0.05). The distal MNBI showed good diagnostic potential. Conclusions Clear pathological alterations, which are distinct from those of other FGIDs, are observable in RH. It might be inappropriate to categorize RHs within FGIDs.